Use of Mitomycin C in Ocular Surgery; A Narrative Review - Mahar, P. S. (Pakistan Journal of Ophthalmology, 2019)
Mitomycin C is an alkylating agent with an anti-proliferative activity. Because of its potent anti-fibroblastic effect, it is used in multiple ocular surgical procedures where inhibition of proliferation of fibroblasts and vascular ingrowths is required. It is dispensed in blue violet crystalline powder and it dissolves in water. MMC is stable for 2 weeks when refrigerated at 2 ? 8 degrees centigrade after the powder is reconstituted for topical use. Because of its anti-fibroblastic activity, MMC is used in various ocular surgical procedures. The optimal dose of MMC is not known but is usually used in concentration of 0.1 mg/ml (0.01%) to 0.5 mg/ml (0.05%) in different clinical setups. Key Words: Mitomycin C, Fibroblasts, Ocular Surgery.